2013
DOI: 10.1074/mcp.m113.028688
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Binary Virus–Host Interactions Using an Infectious Protein Complementation Assay

Abstract: A precise mapping of pathogen-host interactions is essential for comprehensive understanding of the processes of infection and pathogenesis. The most frequently used techniques for interactomics are the yeast two-hybrid binary methodologies, which do not recapitulate the pathogen life cycle, and the tandem affinity purification mass spectrometry co-complex methodologies, which cannot distinguish direct from indirect interactions. New technologies are thus needed to improve the mapping of pathogen-host interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 55 publications
2
75
0
Order By: Relevance
“…PD1 prevented viral RNA export from the nucleus, a crucial step in viral replication, by disrupting viral RNA binding to NXF1, an mRNA transporter. This observation is supported by two high-throughput studies: A genome-wide RNAi screen showed that NXF1i sessential for viral replication (92), and a proteomic study identified it as a cellular interacting partner of the influenza viral polymerase complex (93). …”
Section: Systems Analysis Of Infectious Disease: Influenza As a Case mentioning
confidence: 81%
“…PD1 prevented viral RNA export from the nucleus, a crucial step in viral replication, by disrupting viral RNA binding to NXF1, an mRNA transporter. This observation is supported by two high-throughput studies: A genome-wide RNAi screen showed that NXF1i sessential for viral replication (92), and a proteomic study identified it as a cellular interacting partner of the influenza viral polymerase complex (93). …”
Section: Systems Analysis Of Infectious Disease: Influenza As a Case mentioning
confidence: 81%
“…As such, a molecular understanding of how each viral protein co-opts and interferes with cellular processes during infection is critical for the elucidation of mechanisms of pathogenesis and for the development of novel therapeutic strategies. To gain insight into virus-host protein interactions, studies have been performed using yeast 2-hybrid systems, complementation assays, or affinity purification of epitope tagged viral proteins transfected into cells (Bradel-Tretheway et al, 2011; de Chassey et al, 2013; Gorai et al, 2012; Guan et al, 2012; Jorba et al, 2008; Lin et al, 2012; Mayer et al, 2007; Munier et al, 2013; Ngamurulert et al, 2009; Shapira et al, 2009; Tafforeau et al, 2011). Although these approaches have indicated potential cellular factors targeted by viral proteins, they are limited by the fact that the mere expression of influenza proteins does not recapitulate key physiological aspects of the host-virus battleground.…”
mentioning
confidence: 99%
“…The pCI-PA-LL-Gluc1 plasmid and its derivatives (pCI-PA214P-Gluc1, pCI-PA216P-Gluc1, pCI-PA219P-Gluc1, and pCI-PA223P-Gluc1) and pCI-PB1-SL-Gluc2 plasmids were obtained via modification of pCI-PA and pCI-PB1 by using standard PCR, site-directed mutagenesis, and cloning procedures in order to fuse the following sequences to the 3= end of the PA ORFs and PB1 ORF: a long peptidic linker, AAAGGGGSGGGGS (LL), followed by Gluc1 for PA and a short peptidic linker, AAAGGS (SL), followed by Gluc2 for PB1. The Gateway-derived Gluc2-IPO5 expression plasmid was described previously (34). 293T cells were seeded at a concentration of 3 ϫ 10 4 cells per well in 96-well white plates (Greiner Bio-One, Courtaboeuf, France).…”
Section: Methodsmentioning
confidence: 99%
“…The deficiency of PA-PB1 targeting the nucleus at nonpermissive temperatures may be due to instability of the PA-PB1 complex and/or to inefficient binding to the ␤-importin IPO5, previously shown to be involved in the nuclear import of the PA-PB1 complex (29,38). To investigate these hypotheses, we used a Gaussia princeps luciferase-based complementation assay (33,34) to quantify the binding of PA mutants to PB1 at permissive (35°C) and nonpermissive (39.5°C) temperatures. Figure 8 shows that all the mutations tested (L214P, D216P, L219P, and F223P) impaired the binding with PB1 at both temperatures and that this defect was more pronounced at 39.5°C than at 35°C.…”
Section: Methodsmentioning
confidence: 99%